Impulsive Buying dan Hoarding pada Mahasiswa - Maghfiroh, Qonitatul -; Mangestuti, Retno - (Forum Bisnis Kewirausahaan, 2024)
The phenomenon of impulsive buying and hoarding among university students are two aspects of consumer behavior that significantly affect individuals' financial and psychological well-being. This study aims to explore the correlation between these two behaviors among college students. The research sample consisted of 97 college students who underwent a survey using two instruments, namely the Impulsive Buying Scale (IBS) and the Saving Inventory-Revised (SI-R) to measure the level of hoarding tendencies. The results of this study surprisingly showed no significant relationship between impulsive buying behavior and hoarding tendencies experienced by college students. These findings provide a deeper understanding of the diversity of consumer behavior among college students and emphasize the need for an individualized approach to addressing consumer behavior issues. Key word : hoarding, impulsive buying, student